PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN HOTEL BAGA DESA LAGUNDRI KECAMATAN LUAHAGUNDRE MANIAMOLO KABUPATEN NIAS SELATAN - Sri Indah Nehe (Universitas Nias Raya, 2022)
The purpose of this study was to determine the effect of service quality on customer satisfaction of BAGA Hotel Lagundri Village, Luahagundre Maniamolo District, South Nias Regency. The type of research used is a causal quantitative type. The source of the data was from customers, with the population and sample in this study being 83 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study showed that the calculated value of 5,410 > ttabel 1,664. This research can be concluded that there is an influence of service quality on customer satisfaction of BAGA Hotel Lagundri Village, Luahagundre Maniamolo District, South Nias Regency. The suggestions of this research are (1) Baga Baga Hotel, Lagundri Village, is more active in making changes to the interior design of rooms such as tangible, constraints, responsiveness, assurance and certainty, and empathy as indicators of service quality. (2) Maintain and improve the reliability of employees through accuracy and speed in performing services to staying guests.